PENGARUH KOMPENSASI TERHADAP KINERJA KARYAWAN SWAYALAN BERKAT KASIH TELUKDALAM KABUPATEN NIAS SELATAN - Dohude, Osisio (Jurnal Ilmiah Mahasiswa Nias Selatan, 2023)
The purpose of this study was to determine the effect of compensation on the performance of the employees of the Supermarkets, Berkat Kasih Telukdalam, South Nias Regency. This type of research is quantitative research. The sample used in this study amounted to 32 people. The data analysis method used is simple linear regression analysis. The results of this study indicate that there is a significant influence between the compensation variable on the performance of the employees of the Self-Services Thanking Telukdalam South Nias Regency. In this study obtained a simple linear regression equation, namely Y = 19.246 + 0.634X obtained tcount (7.242) > ttable (1.697) with a significant level of 0.000 <0.05. Then the R square value is 0.636 or 63.6%.